INTEGRATED MANAGEMENT OF SOLID HOUSEHOLD WASTES' TREATMENT - Коніцула, Т.Я.; Довганик, М.С. (Proceedings of National Aviation University, 2012)
The influence of solid household wastes on the environment in Ternopil region was investigated. This ecological assessment of solid household wastes polygons located within the region. The analysis of the effectiveness of collection and sorting of waste as secondary raw materials was performed.